2021
DOI: 10.1523/jneurosci.0081-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Dependent Control of Sensory Neuron Function Regulates Posture Behavior in Drosophila

Abstract: All what we see, touch, hear, taste or smell must first be detected by the sensory elements of our nervous system. Sensory neurons, therefore, represent a critical component in all neural circuits and their correct function is essential for the generation of behaviour and adaptation to the environment. Here we report that the evolutionarily-conserved microRNA (miRNA) miR-263b, plays a key behavioural role in Drosophila melanogaster through effects on the function of larval sensory neurons. Several independent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…miRNA locus miR‐iab 4/8, along with the Hox gene Ultrabithorax, has been reported to affect the self‐righting behavior in the morphologically distinct larval as well as adult stages of Drosophila melanogaster (Issa et al, 2019; Picao‐Osorio et al, 2015). miRNAs also regulate many larval neuronal functions and dynamically complex male courtship behaviors in Drosophila (Iftikhar et al, 2019; Klann et al, 2021). Several studies report miRNAs, including miR‐323a, miR‐26a‐3p, miR‐34, miR‐135a, and miR‐101a, which target mRNAs functioning in different brain regions, affecting pathways culminating in anxiety or depression‐like symptoms in model organisms (Cohen et al, 2017; Fiori et al, 2021; Haramati et al, 2011; Li et al, 2021; Mannironi et al, 2018).…”
Section: Mechanisms Of Non−coding Rnas In Behavioral Pathwaysmentioning
confidence: 99%
“…miRNA locus miR‐iab 4/8, along with the Hox gene Ultrabithorax, has been reported to affect the self‐righting behavior in the morphologically distinct larval as well as adult stages of Drosophila melanogaster (Issa et al, 2019; Picao‐Osorio et al, 2015). miRNAs also regulate many larval neuronal functions and dynamically complex male courtship behaviors in Drosophila (Iftikhar et al, 2019; Klann et al, 2021). Several studies report miRNAs, including miR‐323a, miR‐26a‐3p, miR‐34, miR‐135a, and miR‐101a, which target mRNAs functioning in different brain regions, affecting pathways culminating in anxiety or depression‐like symptoms in model organisms (Cohen et al, 2017; Fiori et al, 2021; Haramati et al, 2011; Li et al, 2021; Mannironi et al, 2018).…”
Section: Mechanisms Of Non−coding Rnas In Behavioral Pathwaysmentioning
confidence: 99%
“…MiRNA biogenesis begins with the processing of RNA polymerase II/III transcripts, occurring concurrently or post-transcriptionally [ [16] , [17] , [18] , [19] ]. A substantial number of miRNAs are derived from introns or specific protein-coding genes (intragenic), while others are intergenic, transcribed independently [ [20] , [21] , [22] , [23] ].…”
Section: Mirna Biogenesis and Functionsmentioning
confidence: 99%
“…Recent work in our laboratory has shown that miRNAs -which are short regulatory non-coding RNAs that repress the expression of target genes [1,2] -have pervasive roles in the articulation of complex movement sequences such as those involved in body posture control in the young Drosophila larva [3][4][5][6]; these observations, as well as those from others in Drosophila and other systems [7][8][9][10][11] hinted at the possibility that these non-coding RNA molecules might also be involved in the control of more fundamental aspects of motor development and control. To explore this question, we first searched for miRNAs that might affect the simple locomotor patterns of the Drosophila first instar larva.…”
Section: A Mirna That Impacts Larval Movementmentioning
confidence: 99%